Revolusi Korea : Dari Pemerintahan Militer Ke Demokrasi (1980-1987) - Mubarak, Mahlijar Azhar; Samsudin, Didin; Triarisanti, Risa (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2024)
The ginseng country of South Korea, which is now one of the 'Asian Tigers', has historically had a difficult journey to become a democratic country. This is shown by the Gwangju tragedy in 1980 and the Korean Revolution in 1987. For this reason, the purpose of this paper is to explore how two important events in South Korea's history in upholding democracy and overthrowing authoritarian governments. The research method used is the historical method with a series of stages starting from data collection (heuristics), source criticism, interpretation and historiography. The research problem consists of: what factors are the background, then how the course of events and its impact on the socio-political life of the South Korean nation. The results showed historical wounds that led to the Korean Revolution in 1987. The Gwangju tragedy ended military rule and turned Korea into an inclusive democracy, characterised by political reform and democratic presidential elections. Both events have helped to realise human rights, in addition to encouraging positive socio-political changes for South Korea